Penerapan Metode Inkuiri pada Mata Pelajaran Penjasorkes untuk Meningkatkan Teknik Bermain Bola Tangan pada Siswa Kelas VI SD Negeri 1 Marga Mulya Tahun Pelajaran 2019/2020: Application of the Inquiry Method in Physical Education Subjects to Improve Handball Playing Techniques for Class VI Students at SD Negeri 1 Marga Mulya for the 2019/2020 Academic Year - Harun, Harun (Anterior Jurnal, 2022)
Physical education is an educational process that utilizes systematic, planned physical activities to develop and improve individuals organically, neuromuscularly, perceptually, cognitively, and emotionally within the framework of the national education system. The problem to be studied in this research is the improvement of physical education learning achievement for students by applying the inquiry method? (b) how is the effect of the inquiry method on students' learning motivation? The results of this study are (a) how is the improvement of physical education learning achievement in students after applying the inquiry method, (b) Knowing the motivation to learn physical education after applying the inquiry method. This research uses two rounds of action research. Each round consists of two stages: design, activity, and observation. Reflection and revision, the subject of this research are Class VI SDN 1 Marga Mulya students from the data obtained in practice test results observation sheets. From the results of the analysis, it was found that student learning achievement increased from cycle I to cycle II, namely, cycle I (65.38%), cycle II (96.15%) for the psychomotor domain, cycle I (69.23%). Cycle II (94.87%) for the affective domain. This study concludes that the inquiry method can positively affect the learning motivation of Class VI students at SDN 1 Marga Mulya, and the learning model can be used as an alternative to physical education.